Home paint exposures and risk of childhood acute lymphoblastic leukemia: findings from the Childhood Leukemia International Consortium - Bailey, H.; Metayer, C.; Milne, E.; Petridou, E.; Infante-Rivard, C.; Spector, L.; Clavel, J.; Dockerty, J.; Zhang, L.; Armstrong, B.; Rudant, J.; Fritschi, Lin; et al. (Kluwer Academic Publishers, 2015)
Purpose: It has been suggested that home paint exposure increases the risk of childhood acute lymphoblastic leukemia (ALL). Methods: We obtained individual level data from eight case–control studies participating in the Childhood Leukemia International Consortium. All studies had home paint exposure data (sometimes including lacquers and varnishes) for the pregnancy period with additional data for the 1–3-month period before conception in five, the year before conception in two, and the period after birth in four studies, respectively. Cytogenetic subtype data were available for some studies. Data were harmonized to a compatible format. Pooled analyses of individual data were undertaken using unconditional logistic regression. Results: Based on 3,002 cases and 3,836 controls, the pooled odds ratio (OR) for home paint exposure in the 1–3 months before conception and risk of ALL was 1.54 [95 % confidence interval (CI) 1.28, 1.85], while based on 1,160 cases and 1,641 controls for exposure in the year before conception, it was 1.00 (95 % CI 0.86, 1.17). For exposure during pregnancy, using 4,382 cases and 5,747 controls, the pooled OR was 1.14 (95 % CI 1.04, 1.25), and for exposure after birth, the OR was 1.22 (95 % CI 1.07, 1.39), based on data from 1,962 cases and 2,973 controls. The risk was greater for certain cytogenetic subtypes and if someone other than the parents did the painting. Conclusions: Home paint exposure shortly before conception, during pregnancy, and/or after birth appeared to increase the risk of childhood ALL. It may be prudent to limit exposure during these periods.